Moğolca'nın İkinci Şahıs Zamirinin Kökeni ve Değişimi - Tömörtogoo, D. (Gökkubbe, 2006)
Moğolcanın şahıs zamirleri hal ekieri ile çekime girdiğinde birbirinden farklı şekiller almaktadır. Bu sebeple Moğolcanın şahıs zamirlerinin kökeni tam olarak aydınlatılamamıştır. Bu makalede Moğolcanın ikinci şahıs zamirinin kökeni açıklanmaya çalışılacaktır. Moğolcanın 2. şahıs zamirinin kökeni ilgi hali eki almış yapılarda aranmalıdır. İlgi hali eki almış yapı aynı zamanda bu zamirin kökenini yansıtmaktadır. The personal pronouns of Mangolian when inflected with case suftixes take different forms. Thus, the origin of personal pronouns of Mangolian couldn't be enlightened precisely. In this article, the origin of second personal pronoun of Mangolian is tried to be revealed. The origin of second personal pronoun of Mangolian must be sought in the structures which have the genitive suffix. A structure with the genitive suffix reflects the origin of this pronoun, too.
The Origin and Transformation of the Second Personal Pronouns of Mongolian
Keywords: Moğolca; Moğolcanın Şahıs Zamirleri; Çi ve Ta'nın Yapısı; Çi ve Ta'nın Kökeni; Çi ve Ta'nın Gelişmesi; Mongolian Personal Pronouns; Mongolian; The Structure of the Çi and Ta; The Origin of the Çi and Ta; The Process of the Çi and Ta